Sofrimento e prazer : uma análise psicodinâmica do trabalho prisional - Bagalho, Jaqueline Oliveira (2015)
This research intends to analyze the psychic suffering as a result of the confrontation between prison security inspectors and the work organization, as well as the intersubjective processes mobilized by these workers in working situations. Therefore, the specific objectives are: to verify how the work organization contributes for the production of suffering and/or pleasure, illness or risk of mental health for these professionals; to seek for the characterization of profession rules regarding the work of prison inspectors, including the prescribed and real rules of its work; to understand how subjective mobilizations interposed in the organization’s dynamic of work have been operated: creativity, cooperation, trust, recognition, and its effects workers’ health-illness process; to identify, through speech, if there are any collective and individual strategies mobilized by the collective of work; and, finally, to analyze how, and if, the Organization uses such defenses strategically or, on the contrary, disarticulates them, and what are its effects on workers' health. According to the psychodynamics of work approach, proposed by Christophe Dejours, the core of the work clinics, overtaken the psychopathology of work, is no longer the suffering, consolidated the whole working situation, but what is done from it, in other words, the psychodynamics of intersubjective processes mobilized by working situations. The method and the analysis of the data on which this research was based is the psychodynamics of work, following three phases: pre-research, research and validation. Nineteen individual interviews were conducted with participants who obtained the characteristics of homogeneous group, through semi-structured script. The data were analyzed through full transcription and verbalization analysis and, afterwards, classified into three axis: work organization, subjective mobilizations and experience of pleasure and suffering. Through data analysis it was found that the collective of prison workers is weakened because of the practice of two kinds of hiring; the collective division seems to affect the mobilizations such as cooperation and recognition, as well as the management practices based on individualism and partisan promotion, instead of meritocratic promotion, suggest reinforcement of these exhibitions of little supportive and cooperative work demonstrations, promoting the exploitation defenses; defenses and strategies tend to be restricted according to the division of the group (contract), mediated by different forms of hiring, preventing it from being widely shared by the collective, so that the mobilizations and individual defenses are more evident than the collective; among the exceptions, the defense ideology against fear proves to be shared by the collective in an homogeneous way. The pleasure experienced by a certain share of the participants seem to be associated with the production of meaning of work more focused on the transformation and social reintegration of the convicted, which is associated with the strengthening of identity when it is in accordance with personal fulfillment.